Pola Komunikasi Mahasiswa Muslim di Kampus Kristen - Dina Fauziyah; Erik Setiawan (Bandung Conference Series: Public Relations, 2022)
Abstract. Researchers are interested in doing this research because of the phenomenon of Muslim students who decide to study at one of the private universities in the city of Bandung which is affiliated with Christianity. science development. The purposes of this study are 1) To find out the motives of communication by Muslim students of the Faculty of Economics at Maranatha Christian University, 2) To find out the meaning of communication by Muslim students from the Faculty of Economics at Maranatha Christian University. This study uses qualitative research with a phenomenological study approach method that functions to deepen information from individual experiences obtained from the speakers regarding the communication patterns of Muslim students of the Faculty of Economics at Maranatha Christian University. Data collection techniques in this study were in the form of observation, in-depth interviews with 4 informants, and literature study. By using source triangulation collection techniques. The result of this research is that the communication motives of Muslim students of the Faculty of Economics at Maranatha Christian University are divided into 2 (two) types, namely Because of Motive or the "cause" motive and In Order to Motive or the "goal" motive. In Because Of Motive, there are motives owned by Muslim students such as the influence of friends, good campus accreditation and majors, included in the favorite campus category and because they did not pass the PTN. While in the In Order to Motive type, that is because of the interest, encouragement and direction of parents, friend relations, and there is a sense of wanting to socialize in the majority environment. Then on the meaning of communication, namely the existence of a high level of tolerance for non-Muslim majority students towards minority Muslim students, and there is new cultural knowledge in the majority environment. Abstrak. Peneliti tertarik melakukan penelitian ini dikarenakan adanya fenomena terhadap mahasiswa muslim yang memutuskan untuk berkuliah di salah satu perguruan tinggi swasta di Kota Bandung yang berafiliasi dengan kristen.salah satunya pada Fakultas Ekonomi di Universitas Kristen Maranatha terdapat cukup peminat mahasiswa yang memilih Kampus ini sebagai tempat belajar dan pengembangan ilmu pengetahuan. Tujuan dari penelitian ini yaitu 1) Untuk mengetahui motif komunikasi yang dilakukan mahasiswa muslim Fakultas Ekonomi di Universitas Kristen Maranatha, 2) Untuk mengetahui makna komunikasi mahasiswa muslim Fakultas Ekonomi di Universitas Kristen Maranatha.. Penelitian ini menggunakan penelitian kualitatif dengan metode pendekatan studi fenomenologi yang berfungsi untuk memperdalam informasi dari pengalaman – pengalaman individu yang didapat dari para narasumber mengenai pola komunikasi mahasiswa muslim Fakultas Ekonomi di Universitas Kristen Maranatha. Teknik pengumpulan data dalam penelitian ini berupa observasi, wawancara secara mendalam terhadap 4 informan, dan studi pustaka. Dengan menggunakan teknik pengumpulan triangulasi sumber. Hasil dari penelitian ini bahwa motif komunikasi mahasiswa muslim Fakultas Ekonomi di Univeritas Kristen Maranatha yang terbagi menjadi 2 (dua) tipe yaitu Because of Motive atau motif “sebab” dan In Order to Motive atau motif “tujuan”. Pada Because Of Motive yaitu terdapat motif yang dimiliki oleh mahasiswa muslim seperti pengaruh teman, Akreditasi kampus dan jurusan yang baik, termasuk dalam kategori kampus favorite dan dikarenakan tidak lolos PTN. Sedangkan dalam tipe In Order to Motive yaitu karena adanya ketertarikan, dorongan dan arahan orangtua, relasi teman, dan ada rasa ingin bersosialisasi di lingkungan mayoritas. Lalu pada makna komunikasi yaitu adanya tingkat toleransi yang tinggi mahasiswa non – muslim mayoritas terhadap mahasiswa muslim minoritas, dan terdapat pengetahuan budaya baru di lingkungan mayoritas.